2007
DOI: 10.1007/s11703-007-0040-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of photoperiod and melatonin on nitrogen partitioning and production performance of Inner Mongolia White Cashmere Goats

Abstract: the shortening of photoperiod and were higher in the implanted groups than in the non-implanted groups, and there was a strong interaction between SDPP and MT implantation; prolactin, insulin like growth factor I and leptin showed the opposite results to MT and INS. This study provides evidence that MT and photoperiod can be used to regulate nitrogen partitioning, modulate cashmere goat body composition and improve cashmere production in practice. The technique can be extended to Inner Mongolia and other cashm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 6 publications
4
14
0
Order By: Relevance
“…The effects of melatonin implants on cashmere fibre diameter have not been consistent. Our study showed that melatonin implants decreased cashmere fibre diameter, which is in agreement with the finding of Wang et al [23]. In contrast, Wuliji et al [20] reported that melatonin treatment increased the fibre diameter in Spanish goats while other studies have shown that administration of melatonin has no effects on cashmere fibre diameter in Inner Mongolian cashmere goats [13, 15, 21], Liaoning cashmere goats [22] or New Zealand cashmere goats [19].…”
Section: Discussionsupporting
confidence: 94%
“…The effects of melatonin implants on cashmere fibre diameter have not been consistent. Our study showed that melatonin implants decreased cashmere fibre diameter, which is in agreement with the finding of Wang et al [23]. In contrast, Wuliji et al [20] reported that melatonin treatment increased the fibre diameter in Spanish goats while other studies have shown that administration of melatonin has no effects on cashmere fibre diameter in Inner Mongolian cashmere goats [13, 15, 21], Liaoning cashmere goats [22] or New Zealand cashmere goats [19].…”
Section: Discussionsupporting
confidence: 94%
“…One subgroup of each group was implanted with melatonin at a dose of 1.86 mg/kg BW (Welch et al, 1990), the another was the control. The three groups were treated with a long-day photoperiod, natural day photoperiod and short-day photoperiod in three adjacent light-controlled rooms, respectively.…”
Section: Animals Experimental Period and Designmentioning
confidence: 99%
“…It was found that altering the photoperiod and implanting melatonin had potential use in Cashmere goat feeding (Wang, 2005). Studies indicated that Cashmere could be induced by implanting melatonin or shortening the photoperiod, and both have an additive effect on cashmere production combined with variations in a series of hormones.…”
Section: Introductionmentioning
confidence: 99%
“…The secretion of MEL in cashmere goats shows distinct cyclical changes with photoperiod, and this cycle is consistent with the growth cycle of cashmere. Studies have shown that MEL is a critical intermediary between photoperiod and cashmere growth, and the greater level of MEL secreted by the pineal gland during times of short daily photoperiod may be the key factor for cashmere growth via increasing the activity of SHFs [11,1315]. Previous studies have shown that the photoperiod is associated with mammary development consistent with the enhancement of milk yield in the ensuing lactation [1618].…”
Section: Introductionmentioning
confidence: 99%